2022
DOI: 10.1108/meq-12-2021-0279
|View full text |Cite
|
Sign up to set email alerts
|

How health consciousness and social consciousness affect young consumers purchase intention towards organic foods

Abstract: PurposeThis current research investigates antecedents affecting young consumers' purchasing intention of organic foods in a developing nation’s (Pakistan) context utilizing Theory of Planned Behavior. For this purpose, theoretical framework comprising characteristics of a product, concerns of consumers and consciousness were proposed.Design/methodology/approachResponses were collected from a sample comprising 418 young consumers through the convenience sampling technique. The data has been evaluated through St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…Healthiness has become an important factor influencing people’s attitudes toward food consumption [ 36 ]. The degree to which individuals prefer to undertake, and are active in managing healthy behaviors, is referred to as health-consciousness [ 16 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthiness has become an important factor influencing people’s attitudes toward food consumption [ 36 ]. The degree to which individuals prefer to undertake, and are active in managing healthy behaviors, is referred to as health-consciousness [ 16 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A previous study showed that the number of overweight adolescents (young adults) has increased, leading to physical health problems [ 36 ]. They were influenced to indulge by several factors, one of which was from parents, as they have less time to prepare nutritious meals [ 37 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The attitude of choosing and buying organic foods is guided by the health benefits that this type of food can bring with emphasis on its superior quality compared to industrialized products (Bian and Forsythe, 2012;Farias et al, 2019). In this sense, public health campaigns MEQ 34,5 are currently being developed to promote the benefits of a healthy diet and to encourage individuals (consumers) to have favorable attitudes to make healthy nutritional and dietary decisions (Su et al, 2022;Plows et al, 2017).…”
Section: Research Hypotheses and Proposed Theoretical Modelmentioning
confidence: 99%
“…In addition, in consumer psychology research, attitude has been regarded for a long time as the most influential factor in influencing the behavioral intention and actual behavior. It could disclose customers' psychological evaluations of a product (Su et al, 2022). In addition, research indicates that, in terms of CaRM, corporate philanthropy influences customers' actual and prospective favorable attitudes toward businesses, which, in turn, influences their loyalty to those businesses' products and services and subsequent actions (Yen and Yang, 2018).…”
Section: Effect Of Carm On the Customers' Pi 1121mentioning
confidence: 99%